Making a Collection Count : a Holistic Approach to Library Collection Management. - Hibner, Holly; Kelly, Mary (Chandos information professional series., 2010)
Making a Collection Count takes a holistic look at library collection management. It connects the various pieces, such as selection, cataloguing, shelving, circulation, and weeding and teaches readers how to gather and analyze data from each point in a collection's life cycle. Relationships between collections and other library services, such as reference, programming, and technology, are explored as well. The result is a quality collection that is clean, current, relevant, and useful, and which connects and highlights various library services.